Mendefinisikan ulang keterampilan dan kompetensi pustakawan untuk mendukung ekosistem investasi di Indonesia: studi kasus di perpustakaan BSN - Muhammad Bahrudin; Nursidik Fadillah (Faculty of Communication, Padjadjaran University, 2021)
The Indonesian Government has made various efforts to increase investment, mainly through deregulation. One of the implementations of these deregulation efforts is the development of the One-Stop Service Center (PTSP) at the Ministry of Investment/BKPM as an integrated service center for licensing and non-licensing activities related to investment, Foreign Investment (PMA), and Domestic Investment (PMDN). Badan Standardisasi Nasional (BSN) took part in providing service counters at the Central PTSP to provide services in the field of Standardization and Conformity Assessment (SPK). The implication is that BSN requires competent human resources to support these services. Currently, the personnel assigned to the Central PTSP is a librarian. This study aims to identify the skills and competencies needed by librarians to support the investment ecosystem in Indonesia through Central PTSP services. This study was designed by qualitative research with a case study method. Data collection methods using literature study and in-depth interview. This paper focused on the case of a BSN librarian as an informant who was assigned as a liaison officer at the Central PTSP. Data analysis was carried out using a descriptive method. Findings in this study highlight that librarians in special libraries need to improve and adopt 11 (eleven) skills and competencies that are relevant to the duties and functions of the institution, as well as an investment ecosystem to produce optimal librarian performance for the parent institution and society in general. The conclusions of the study include; First, special libraries have different resource tendencies from one institution to another which have an impact on different needs for skills and competencies. Second, special libraries can synergize with institutions outside the parent institution to meet the information needs of segmented users. Third, librarians in special libraries are very important to be subject specialists in their institutional environment. Fourth, the skills and competencies experienced by librarians in special libraries can be overcome by various strategic steps.